Analysis of the Effect of Tax Compliance, Electronic Tax Reporting Systems, and Management Perceptions on the Effectiveness of Tax Planning Strategies in Manufacturing Companies in Jakarta - Judijanto, Loso; Nurina, Lia (Westscience Press, 2024)
This study explores the intricate interplay of tax compliance, electronic tax reporting systems (ETRS) usage, and management perceptions in shaping tax planning effectiveness in Jakarta's manufacturing companies. Using a quantitative approach, a survey collected responses from 115 manufacturing enterprises, analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). Significant positive correlations were found between tax compliance and ETRS usage, ETRS usage and tax planning effectiveness, and management perceptions and tax planning effectiveness. ETRS usage emerged as a mediator in the relationship between tax compliance and tax planning effectiveness, while management perceptions acted as a moderator in the link between ETRS usage and tax planning effectiveness. The study provides valuable insights into the dynamics influencing tax planning in the manufacturing sector, suggesting a synergistic approach for practitioners and offering policymakers guidance on technology adoption and ethical considerations in tax planning.